2012
DOI: 10.3109/17482968.2012.692382
|View full text |Cite
|
Sign up to set email alerts
|

Speech therapy and communication device: Impact on quality of life and mood in patients with amyotrophic lateral sclerosis

Abstract: Dysarthria has a drastic impact on the quality of life of ALS patients. Most patients suffering from dysarthria are offered speech therapy. Communication devices are prescribed less frequently. In the present study we investigated the impact of these therapeutic arrangements on quality of life in ALS patients. Thirty-eight ALS patients with dysarthria or anarthria, who underwent speech therapy and/or used communication devices answered three standardized questionnaires (Beck Depression Inventory - II (BDI), SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 12 publications
1
50
0
3
Order By: Relevance
“…Three studies were RCTs [24][25][26], two were cohort studies [27,28] and one was a cross-sectional study [29]. Five studies reported SF-36 [24,25,[27][28][29] and one study reported ALSAQ-40 [26]. There were no disagreements between the authors for included studies; using Cohen's Kappa [16], the level of agreement was calculated as 1, representing perfect agreement.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies were RCTs [24][25][26], two were cohort studies [27,28] and one was a cross-sectional study [29]. Five studies reported SF-36 [24,25,[27][28][29] and one study reported ALSAQ-40 [26]. There were no disagreements between the authors for included studies; using Cohen's Kappa [16], the level of agreement was calculated as 1, representing perfect agreement.…”
Section: Resultsmentioning
confidence: 99%
“…Of the five studies reporting SF-36 [24,25,[27][28][29], three were RCTs, and 2 were non-RCTs. Two RCTs which focused on exercise enrolled 25 and 27 ALS patients respectively [24,25].…”
Section: Description Of Studies and Effect Of Rehabilitation Intervenmentioning
confidence: 99%
See 3 more Smart Citations